Studi Kasus Intervensi Coaching Dan Konseling Untuk Meningkatkan Kompetensi Kepemimpinan - Lindriani, Nofita; Nugroho, Opi; Surya, Eka Putri Amelia (CV. ITTC INDONESIA, 2024)
This assessment process aims to diagnose problems that occur in the General and Personnel Subdivision. The subjects involved in this study amounted to 4 people consisting of the Secretary of the Regional Civil Service Agency, the Head of the General and Personnel Sub-Division, and the Employees of the General and Personnel Sub-Division. The assessment method used is interviews and document studies. Based on the results of the analyst, it was found that problems related to the performance of the General and Personnel Sub Division are related to the lack of competence of leaders. This is related to managerial competence and personal competence, so that the work does not look optimal. In addition, there is dissatisfaction among group members due to the lack of interpersonal skills possessed by leaders.